X-ray computed tomography in dendrochronology studies; 9th International Topical Meeting on Industrial Radiation and Radioisotope Measurement Applications, Valencia, July 6-11, 2014 - Stuchebrov S. G. Sergey Gennadevich; Batranin A. V. Andrey Viktorovich; Bondarenko S. L.; Sapozhnikova V. A. (2014, 2014)
В фонде НТБ ТПУ отсутствует